Optimized precipitation process for the treatment of radioactive effluents from Ni-alloy decontamination using a chemical oxidation reduction process - Robin, Mathurin; Rivonkar, Aditya; Suzuki-Muresan, Tomo; Abdelouas, Abdesselam; Mokili, Marcel (Frontiers in Nuclear Engineering, 2024)
Nuclear power plays a major role in the generation of electricity with low carbon emissions. However, it generates significant amounts of radioactive waste, mainly from contaminated metallic components such as steam generators. Decontamination is essential for the safe handling and eventual recycling or disposal of these materials. Various decontamination techniques can be utilized but chemical processes are recommended for complex geometries such as the tubular parts of steam generators. COREMIX (Chemical Oxidation REduction using nitric permanganate and oxalic acid MIXture) is a process that is similar to the CORD (Chemical Oxidation Reduction Decontamination) process currently utilized in the industry which involves dissolving the contaminated oxide layers from metallic surfaces. This process generates a large quantity of radioactive effluent that requires appropriate treatment. The objective is to reduce metallic concentration and the radioactivity by precipitating metals in solution as hydroxides M(m-n)(OH)n (with m the oxidation number of the metal M). The optimization of a two-step precipitation protocol is presented here, with a study of the contact time (1 to 24 hours) and the reagents used (NaOH and KOH). The resulting precipitates from this process are characterized using several techniques (FTIR, TGA, XRD). Tests were conducted on surrogate samples to demonstrate the viability of the process on more complex samples. Finally, the optimized protocols were implemented on radioactive Ni-alloy samples. Decontamination factors were calculated portraying the efficiency of both the COREMIX and the subsequent two-stage precipitation process. Characterization of the sludge produced during the process shows that the precipitate obtained at pH 8.5 consists mainly of iron (III) oxide-hydroxides, whereas the precipitate obtained at pH 12 is mainly composed of manganese (II,III) oxide. The optimization steps show that the contact time during the first precipitation and the choice of precipitants does not influence the efficiency of the protocol while the destruction of oxalic acid proves to be critical to quantitatively precipitate chromium. Ultimately, the COREMIX process can effectively decontaminate contaminated Ni-alloy samples, removing between 12 and 14% of the contamination in each cycle. Decontamination of effluent using the precipitation protocol results in a very high decontamination factor of between 3000 and 6000.